1989
DOI: 10.1016/0169-2070(89)90086-1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting job performance: A comparison of expert opinion and research findings

Abstract: A survey was conducted of New Zealand personnel consultants. Their beliefs about the validity of various selection tools and their claimed usage of these tools was then compared with the validities in a previously published meta-analysis. The experts claimed to use the predictors they believed to be most valid. However, their beliefs about validity were unrelated to empirically demonstrated validities (Spearman's rho = -0.06). Suggestions were made on the types of research that are needed to improve predictive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 19 publications
4
30
2
Order By: Relevance
“…This study develops further on the relationships and data reported by Dakin and Armstrong (1989). More specifically, this study seeks to establish: 1 the relationship between: the frequency caf use of managerial selection methods and their perceived validity; the frequency of use of managerial selection methods and their reported validity' coefficients from the research literature; the personnel consultants' perceived validity of the selection methods and their reported validity coefficients.…”
Section: Paul Kilsha Toulsonmentioning
confidence: 94%
See 2 more Smart Citations
“…This study develops further on the relationships and data reported by Dakin and Armstrong (1989). More specifically, this study seeks to establish: 1 the relationship between: the frequency caf use of managerial selection methods and their perceived validity; the frequency of use of managerial selection methods and their reported validity' coefficients from the research literature; the personnel consultants' perceived validity of the selection methods and their reported validity coefficients.…”
Section: Paul Kilsha Toulsonmentioning
confidence: 94%
“…While there have been a number of unpublished studies relating to the level of use of various selection methods in New Zealand (Harris, 1991;Waugh, 1991;, the amount of published research focusing on the management selection methods employed by New Zealand personnel consultants is limited. The most recent published research is Dakin and Armstrong (1989).…”
Section: Paul Kilsha Toulsonmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite much research evidence, practitioners still ignore the findings. As shown by Ahlburg (1991) and Dakin and Armstrong (1989), they even continue to rely on judgment for personnel predictions, the subject of much of this research.…”
Section:  Use Quantitative Methods Rather Than Judgmental Methods Imentioning
confidence: 99%
“…For example, intelligence is the single best predictor of job performance (Schmidt and Hunter 1998), yet only 18 percent of the 959 HR professionals surveyed by Rynes et al (2002) identified intelligence as a better predictor of job performance than conscientiousness. Similarly, when personnel experts in New Zealand and the United States were asked to rank the strength of job-performance predictors, the correlation between the experts' rankings and the evidence-based rankings was close to zero (Ahlburg 1992;Dakin and Armstrong 1989). Two surveys of 820 British recruitment consultants found that executives are generally selected using unstructured interviews and character references, procedures with little validity (Clark 1992).…”
Section: Does Higher Pay Lead Firms To Hire More Effective Executives?mentioning
confidence: 99%